Upaya Penumbuhan Karakter dan Disiplin Peserta Didik Melalui Program Sekolah Apel Pagi dan Dhuha Wajib di SMK Muhammadiyah 1 Sukoharjo - Ana Setiyaningrum; Aryo Danurwindo; Suyahman Suyahman (CIVICS EDUCATION AND SOCIAL SCIENCE JOURNAL (CESSJ), 2023)
This study aims to foster the disciplined character of students through the Morning Apple and Dhuha Prayer school programs in the Muhammadiyah 1 Vocational School, Sukoharjo. In this study, the authors used data collection techniques, namely samples in class XI PPLG 1, XI PPLG 2, and XI PPLG 3. In this study, it was concluded that the Morning Apple and Dhuha Prayer school programs were effective in an effort to foster the disciplined character of students in SMK Muhammadiyah 1 Sukoharjo especially in class XI PPLG 1, XI PPLG 2, XI PPLG 3. The research methodology used is descriptive qualitative with an emphasis on depicting the description of the school's program being implemented. The conclusion obtained is that the morning apple program at Muhammadiyah 1 Vocational School Sukoharjo aims to foster the character of discipline and the spirit of work ethic while the Dhuha Obligatory program fosters the character of discipline in increasing religious activity and piety to Allah swt.Keywords: Character of Discipline, PPKn, School Program, SMK Mutuharjo